The Effect of Audio Visual Media on The Value of Humanity and Pro-Social Behavior of Students Class 5, SD Negeri Cilibur 04 Kabupaten Brebes on Civics Subjects - Faiq Muamar; Ana Andriani (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Education plays a crucial role in shaping human personality, fostering good morals, and supporting overall personal growth, leading to smoother life experiences. The prevalence of antisocial behaviors such as bullying, promiscuity, and drug use among teenagers can be attributed to a lack of diverse values and prosocial behavior. Socio-economic differences among various classes, including civil servants, entrepreneurs, and laborers, further emphasize the need for understanding diversity values to create peace and harmony among students. This study utilizes primary data and focuses on 30 fifth-grade students from SDN Cilibur 04. The relationship between Audio Visual Learning and the understanding of diversity values shows a significant value of 0.000 (p < 0.05), indicating a notable difference in understanding these values among students who use audio-visual learning media. Similarly, the relationship between Audio Visual Learning Media and prosocial behavior also reveals a significant value of 0.000 (p < 0.05), demonstrating a difference in prosocial behavior between students who engage with audio-visual learning methods. The results of this research conclude that: 1) There is a significant difference in the understanding of diversity values among fifth-grade students at SDN Cilibur 04 when using audio-visual learning methods, with a significance value of 0.000. 2) There is a significant difference in prosocial behavior among fifth-grade students at SDN Cilibur 04 when employing audio-visual learning methods, with a significance value of 0.000.